2022
DOI: 10.1038/s41699-022-00340-6
|View full text |Cite
|
Sign up to set email alerts
|

An ab initio study on resistance switching in hexagonal boron nitride

Abstract: Two-dimensional materials have been widely investigated to implement memristive devices for data storage or neuromorphic computing applications because of their ultra-scaled thicknesses and clean interfaces. For example, resistance switching in hexagonal boron nitride (h-BN) has been demonstrated. This mechanism is most of the time attributed to the movement of metallic ions. It has however also been reported when h-BN is contacted with two inert electrodes such as graphene or Pt. We suggest here that the swit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 40 publications
4
20
0
Order By: Relevance
“…Our DFT study also showed many other types of defects that are stable and hence could be generated by electrical stress and contribute to the leakage current; a finding supported by our experimental observation that only ∼30% of the above mentioned CAFM I-V curves show electrical shorting of the h-BN layer behavior, with presumably the other 70% of the observations representing the effect of alternative defect configurations . A recent extension of the DFT approach demonstrated that resistive switching in h-BN for use in memristor devices may also be based on the reversible formation of such molecular bridge defects, at least for the case studied involving tri-vacancy defects . Importantly for our study, this work also showed that the electronic transmission function of the bridge-type defects is ∼1000× greater than that of pristine h-BN, indicating that a significant increase in charge transfer would occur through these bridge defects.…”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…Our DFT study also showed many other types of defects that are stable and hence could be generated by electrical stress and contribute to the leakage current; a finding supported by our experimental observation that only ∼30% of the above mentioned CAFM I-V curves show electrical shorting of the h-BN layer behavior, with presumably the other 70% of the observations representing the effect of alternative defect configurations . A recent extension of the DFT approach demonstrated that resistive switching in h-BN for use in memristor devices may also be based on the reversible formation of such molecular bridge defects, at least for the case studied involving tri-vacancy defects . Importantly for our study, this work also showed that the electronic transmission function of the bridge-type defects is ∼1000× greater than that of pristine h-BN, indicating that a significant increase in charge transfer would occur through these bridge defects.…”
Section: Introductionsupporting
confidence: 80%
“…Such defects have been termed molecular bridges by Strand et al 31 and our DFT results reveal three bridge structures corresponding to the lowest formation energies among all structures considered in our study. As such, we postulate that the generation of such molecular bridge defects contribute significantly to the observed out-of-plane charge transfer and electrical shorting between layers, an assumption supported by the electronic transmission calculations of Ducry et al 32 The presence of such molecular bridges across the van der Waals gap between adjacent h-BN layers thus provides charge transport 'highways' that facilitate vertical current flow across the h-BN stack. We cannot fully confirm yet whether the three bridge structures are indeed the lowest energetically among all possible defect configurations and charge states, but other defect pairs tend to have much larger formation energy and hence while they may contribute to the charge transfer, these non-bridging defects are presumably smaller in number.…”
Section: Ab Initio Studies Of Stress Induced Defectssupporting
confidence: 57%
See 3 more Smart Citations